Relationship Between Duration of Hemodialysis and Knowledge Level About Chronic Kidney Disease Among Hemodialysis Patients in Kupang City - Betty Griselda Christine Soemoeljo; Teguh Dwi Nugroho; Su Djie To Rante; Elisabeth Levina Sari Setianingrum (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Long-term kidney disease is a worldwide health issue that is becoming more common, leading to numerous individuals needing ongoing hemodialysis treatment. Understanding the illness and the management of hemodialysis is vital for successful treatment and improving life quality. However, the length of time a patient undergoes hemodialysis does not always match their level of understanding about the condition. The aim of this study was to determine the relationship between hemodialysis duration and knowledge levels about chronic kidney disease among hemodialysis patients in Kupang City. The research method used was analytical with a cross-sectional design. Sampling was conducted using purposive sampling according to specific inclusion criteria. Knowledge levels were assessed using the Chronic Kidney Disease Knowledge Questionnaire, while the duration of hemodialysis was gathered from medical records. The data analysis involved univariate and bivariate analysis, utilizing the Chi-square test (p < 0.05). A large portion of the participants were between the ages of 52 to 66 years (41.1%), had completed high school (35.6%), and were either unemployed or retired (36.2%). Regarding the length of hemodialysis, the majority of participants fell into the category of more than 24 months (43.6%). Knowledge levels ranged from good to poor. Bivariate analysis indicated no significant connection between the duration of hemodialysis and the understanding of chronic kidney disease (p-value = 0.500). There is no association between the length of hemodialysis and the understanding of chronic kidney disease among patients receiving hemodialysis in Kupang City.